Integrated Innovation as a Pathway to Organizational Performance: An Empirical Investigation of Nigerian Insurance Industry (International Journal of Business Innovation, 2022)
The study investigates the influence of integrated innovation on organizational performance with specific reference to the Nigerian insurance industry. Specifically, the study examines the association that exists between technology innovation, social innovation, business innovation, and organizational performance. A purposive sample technique was adopted to select 250 respondents from the 10 best insurance companies in Lagos. The data collection instruments for the study were structured questionnaires designed for the study. Path analysis was used to analyse the data with the aid of STATA version 15. The result reveals that technology innovation and business innovation have a positive association with organizational performance but are insignificant, while social innovation has a positive and significant relationship with organizational performance. It was further revealed that technology innovation has a direct correlation with social innovation and social innovation has a linear association with business innovation, while technology also has a significant correlation with business innovation.   Therefore, it is imperative for the sector to fully implement the integrated innovation to enable the number of policyholders to increase from the present 3 million to 60 million by 2030 through mobile phones and the development of applications, blockchain, artificial intelligence, distributed ledger technology, and Robo-advice. Thus, it will go a long way for the sector to have larger coverage.
Keywords: Integrated innovation; technology innovation; social innovation; business innovation; performance